'Her cry is my cry': resettlement experiences of refugee women at risk recently resettled in Australia. (May 2018) - Vromans, L.; Schweitzer, R.D.; Farrell, L.; Correa-Velez, I.; Brough, M.; Murray, K.; Lenette, C.
Abstract: Objectives: Refugee women entering resettlement countries on woman-at-risk visas represent a particularly vulnerable population. While their specific gender-based resettlement will likely differ from the general refugee population, little is known about their experiences of early resettlement, with which to inform resettlement policy and practice. This research aimed to explore lived experiences of recently resettled refugee women at risk in Australia. Study design: Qualitative research used focus groups and a framework approach to identify and explicate common themes in participants' experience. Methods: Two focus groups with a purposive sample of African and Afghan refugee women at risk ( N  = 10), aged 22–53 years, were conducted in South East Queensland, Australia (October 2016), recruited with the assistance of a local resettlement service. Discussions were audiotaped, transcribed, and themes explicated. Results: Six superordinate themes emerged: (1) sentiment of gratitude; (2) sense of loneliness and disconnection; (3) feeling incapable; (4) experiencing distress and help-seeking; (5) experiencing financial hardship; and (6) anticipating the future. Conclusions: Findings indicate that resettlement policy, programs, and practice that explicitly target the needs of women-at-risk refugees are warranted, including a longer period of active service provision with specific attention to strategies that address the women's social connection, self-efficacy, emotional well-being, and financial hardships. Highlights: Successful resettlement of refugee women at risk requires targeted programs. Longer periods of active service delivery may assist women's long-term integration. Programs should connect the women at risk with each other and the host community. Programs should address women's emotional and financial well-being and efficacy.